Katherine Mansfield and periodical culture - Mourant, Chris (Edinburgh University Press, 2019)
This work considers Mansfield's ambivalent position as a colonial woman writer by examining her contributions to the political weekly 'The New Age', the avant-garde little magazine 'Rhythm' and the literary journal 'The Athenaeum'.